FGF21 Mediates Mesenchymal Stem Cell Senescence via Regulation of Mitochondrial Dynamics. (17th April 2019) - Li, Xin; Hong, Yimei; He, Haiwei; Jiang, Guojun; You, Wei; Liang, Xiaoting; Fu, Qingling; Han, Shuo; Lian, Qizhou; Zhang, Yuelin
Abstract : Mesenchymal stem cell- (MSC-) based therapy is a novel strategy in regenerative medicine. The functional and regenerative capacities of MSCs decline with senescence. Nonetheless, the potential mechanisms that underlie their senescence are not fully understood. This study was aimed at exploring the potential mechanisms of fibroblast growth factor 21 (FGF21) in the regulation of MSC senescence. The senescence of MSCs was determined by senescence-associated β -galactosidase (SA- β -gal) staining. The morphology and the level of mitochondrial reactive oxygen species (ROS) of MSCs were assessed by MitoTracker and Mito-Sox staining, respectively. The expression of FGF21 and mitochondrial dynamics-related proteins was detected by Western blotting. As MSCs were expanded in vitro, the expression of FGF21 decreased. Depletion of FGF21 enhanced production of mitochondrial reactive oxidative species (ROS) and increased the senescence of early-passage MSCs whereas inhibition of ROS abolished these effects. The senescent MSCs exhibited increased mitochondrial fusion and decreased mitochondrial fission. Treatment of early-passage MSCs with FGF21 siRNA enhanced mitochondrial fusion and reduced mitochondrial fission. Moreover, treatment of mitofusin2- (Mfn2-) siRNA inhibited depletion of FGF21-induced MSC senescence. Furthermore, we demonstrated that depletion of FGF21-induced mitochondrial fusion was regulated by the AMPK signaling pathway. Treatment with an AMPK activator, AICAR, abrogated the depletion of FGF21-induced senescence of MSCs by inhibiting mitochondrial fusion. Compared with MSCs isolated from young donors, those derived from aged donors showed a lower level of FGF21 and a higher level of senescent activity. Furthermore, overexpression of FGF21 in aged MSCs inhibited senescence. Our study shows that FGF21, via the AMPK signaling pathway, regulates the senescence of MSCs by mediating mitochondrial dynamics. Targeting FGF21 might represent a novel strategy to improve the quality and quantity of MSCs.